Intersecting emergencies: acute adrenal crisis in a patient with acute coronary syndrome - Mitra, Sona; Muley, Arti; Patel, Priyal; Viramgama, Kuldeep; Chaudhary, Hasmukh (International Journal of Advances in Medicine, 2025)
Acute adrenal crisis is a rare but life-threatening endocrine emergency that can present with non-specific symptoms and may mimic or coexist with other critical conditions such as acute coronary syndrome (ACS). We report a case of 48-year-old male with no known comorbidities who presented with left-sided chest pain, restlessness, and gastrointestinal symptoms. He was initially diagnosed with Non-ST Elevation Myocardial Infarction (NSTEMI) and managed for Acute coronary syndrome (ACS) and dyselectrolytemia. Upon referral to our tertiary care centre, the patient was found to have complete heart block, severe hyperkalemia, hyponatremia, and hypotension. Despite correction of hyperkalemia and initiation of standard therapy for ACS with cardiogenic shock, the patient’s condition failed to improve. Further evaluation revealed critically low serum cortisol (1.9 µg/dl) and elevated plasma adrenocorticotropic hormone (ACTH-630 pg/ml), confirming a diagnosis of primary adrenal insufficiency (Addison’s disease) with acute adrenal crisis. Initiation of intravenous hydrocortisone and fludrocortisone led to rapid clinical stabilization, normalization of electrolytes, and improvement in hemodynamic status of the patient. The patient was discharged in stable condition on maintenance corticosteroid therapy. This case highlights the importance of considering adrenal insufficiency in patients with persistent hypotension and dyselectrolytemia, particularly when presenting atypically in the context of acute coronary syndrome.